Participation in algorithmic administrative decision-making (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The purpose of this essay is to assess whether participation in administrative proceedings remains guaranteed even when these proceedings are conducted using algorithms. Algorithmic proceedings tend to be notably streamlined and, as a result, are at a heightened risk of bypassing the legal guarantees of participation. Additionally, the essential function of the individual responsible for overseeing the procedure is scrutinized. By examining both traditional forms of participation and participation within algorithmic contexts, the essay highlights the challenges and opportunities presented by an administration that operates through digital tools.
Keywords: Public administration; administrative; proceedings; algorithms; digitalisation; participation